(3EOGQI GdehGQO GdHTQjI aj GdbWGY GdYGe (B/s - (3MSf, MSGe GHQGgjes ((3YeGf(B: s (3OGQ GdHOGjI(B, s, 2009)
(3JYQja GdefXeI aj GdbWGY GdYGe ,GdJWhQ GdJGQjNj dGOGQI GdehXajf aj GdbWGY GdYGe,GdehGQO GdHTQjI aj GdbWGY GdYGe,GdJfXje GdUfGYj ddbWGY GdYGe,GdGJUGdGJ aj GdGOGQI OGNd GdbWGY GdYGe, JMOjO GdeTcdI GdJNWjWjI ddehGQO GdHTQjI aj GdbWGY GdYGe,WHjYI GdJNWjW OGNd GdbWGY GdYGe,OhQ GOGQI GdehGQO GdHTQjI aj GYOGO GSJQGJjLjI GdeDSSI,OhQ GdehGQO GdHTQjI aj JfajP GSJQGJjLjI GdeDSSI,OhQ GdehGQO GdHTQjI aj JfajP GSJQGJjLjI GdbWGY GdYGe,GdOhdI h GdMcheI h GdehGQO GdHTQjI,GdQbGHI Ydi GdehXajf aj GdbWGY GdYGe,GdSdhc GdJfXjej ddehGQO GdHTQjI aj GdbWGY GdYGes
(3eQGLY U(B.247s
Keywords: (3EOGQI GdehGQO GdHTQjIs; (3GdEOGQI GdYGeIs; (3GdbWGY GdYGes; (3GdehGQO GdHTQjIs